Clinical Spectrum of Hepatitis B in India- A Retrospective Ten Year Study - Malhotra, Parveen; Malhotra, Vani; Gupta, Usha; Sanwariya, Yogesh; Pahuja, Isha; Akshay, . (Highlights on Medicine and Medical Science Vol. 3, 2021)
Introduction: Hepatitis B virus (HBV) infection, a pan global health problem, has already effected one-third of the world population. India harbours around 40 million HBV carriers, thus accounting for 10–15% share of total pool of HBV carriers of the world. Every year over 100,000 Indians die due to illnesses related to HBV infection Aims and Objectives: To study the Epidemiological profile and Clinical spectrum of patients with Hepatitis B virus infection. Materials and Methods: This prospective study was done at Department of Medical Gastroenterology, PGIMS,Rohtak over a period of ten years i.e. 01.09.2010 to 31.08.2020, on HbsAg positive patients who reported on outdoor patient department or were admitted in various wards of hospital. Conclusion: Hepatitis B is having certain hotspots in India like Haryana. The young males with rural background are most vulnerable because of unsafe needle & injection practices due to non-availability of proper health care facilities.